The hidden gifts of helping : how the power of giving, compassion, and hope can get us through hard times - Post, Stephen Garrard, 1951- (Jossey-Bass, 2011)
"The life affirming book that helps us discover how to making 'helping' a lifetime activity. The world's religions affirm it to be so, and recent research across a number of disciplines tell us that 'helping others not only benefits those we assist but is good for us as well.' The recent and astonishingly generous outpouring of help and donations in response to the earthquake in Haiti is a clear demonstration of this phenomenon, but what if we could be convinced to make helping others a way of life, even when times are hard?' Post is author of the widely praised When Good Things Happen to Good People. 'Filled with inspirational anecdotes about the transformative power of doing good.' The author is a leader in the study of altruism, compassion, and love, as well as the President of the Institute for Research on Unlimited Love."--Provided by publisher.